Assessing Knowledge and Attitude in Police Officers Regarding Domestic Violence - Mehreen Fatima, Rafay Ahmed Siddiqui, Ramlah Naz, Arshad Khan, Ravail Aeman Jafri, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the knowledge and attitude in police officers regarding domestic violence. Study Design: Cross-sectional study Place & Duration of Study: Police Training Centre, Saeedabad, Karachi from 1st June to 31st December 2021. Methodology: A questionnaire based study was conducted on 72 Police officers at or above the rank of ASI selected by simple random sampling. Results: There were 65 males and 7 females. 72.3% respondents were unaware of definition of domestic violence per WHO criterion. Majority of respondents were against physical violence in all scenarios. However, 70% held wife responsible to be verbally abused for misbehaving with husband/relatives. No significant association was found between knowledge with variables like age, gender and rank.65% of officers believe that violence should be resolved by family members. Conclusion: Reform and policy changes are needed to train and create awareness in law enforcement agencies to increase their knowledge and modify their attitudes regarding domestic violence.